2018
DOI: 10.2196/preprints.10795
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Community-Based, Point-of-Care Sexually Transmitted Infection Screening Among High-Risk Adolescents in Los Angeles and New Orleans: Protocol for a Mixed-Methods Study (Preprint)

Abstract: Background: Sexually transmitted infection (STI) rates are increasing in the United

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…We anticipate a higher proportion of women in our sample from New Orleans and that while most youth from New Orleans will be African American, youth in Los Angeles will also be Latino and White and predominately GBTY. Further details on each of the ATN CARES studies may be found in the corresponding study protocol papers [112,[115][116][117][118]. Recruitment Process.…”
Section: Peer Support Via Social Mediamentioning
confidence: 99%
“…We anticipate a higher proportion of women in our sample from New Orleans and that while most youth from New Orleans will be African American, youth in Los Angeles will also be Latino and White and predominately GBTY. Further details on each of the ATN CARES studies may be found in the corresponding study protocol papers [112,[115][116][117][118]. Recruitment Process.…”
Section: Peer Support Via Social Mediamentioning
confidence: 99%